An Examination of the Role of the Church on Indigent Nigerian Children - Okoh, Blessing Uenosen; Osagie, Justina U. (NIU Journal of Humanities, 2025)
This study critically examines the role of the Nigerian church in addressing the health needs of indigent Nigerian children through the perspective of James 1:27, which stresses caring for “orphans and widows in their distress. Indigent children in Nigeria are confronted with issues such as poor health, inadequate education and emotional trauma, being aggravated by poverty and underdeveloped healthcare systems. While the church plays a key role in assisting those children, its solutions typically lack the convergence of spiritual, physical and social care needed to address these difficulties all-inclusively. The study therefore examines the theological foundation of the church’s mandate, appraise the impact of its initiatives and identifies gaps in addressing indigent Nigerian health needs. Content analytical approach was adopted. Findings accentuate the necessity for combining spiritual and social care, adopting evidence-based intervention strategies and mobilizing resources to increase the church’s competence. Recommendations include creating alliances, using technology, and improving lobbying for legislation that protect indigent Nigerian children’s rights. This research highlights the potential of the Nigerian church as a life-changing force in strengthening indigent Nigerian children's health and well-being, linking its practical efforts with its theological duty. Keywords:  Examination, Church, Nigerian, Indigent and Children